Integrating ethnomathematics and ethnomodeling in Institutionalization of school mathematics concepts: A study of fishermen community activities - Sudirman; Rodríguez-Nieto, Camilo Andrés; Bonyah, Ebenezer (Journal on Mathematics Education, 2024)
While previous studies have extensively explored ethnomathematics, the relationship between ethnomathematics and ethnomodeling remains underexamined. This study investigates the connections between ethnomathematics and ethnomodeling and their implications for the institutionalization of mathematics in the context of traditional fish auction activities within the Fishermen's Community in Indramayu, Indonesia. Utilizing an ethnographic design, the study involved participants in various auction roles, including auctioneers, boat owners, captains, crew members, and traders. Data were collected through interviews and observations and analyzed using content analysis. The findings reveal that ethnomathematical practices are evident in sorting and grading fish, as well as in auction transactions, with connections to mathematical concepts such as set theory, basic statistics, social arithmetic, and arithmetic operations within an ethnomodeling framework. These results suggest that the integration of ethnomathematics and ethnomodeling into the school curriculum could support the institutionalization of mathematics education and provide a foundation for developing instructional materials based on these practices in the context of traditional fish auctions.